Meta Analisis Studi Kelas Menengah Muslim di Indonesia - M. Yusuf; Afrizal Afrizal; Bob Alfiandi (Indonesian Journal of Religion and Society, 2022)
The emergence of the Islamic populism movement marked by the "212 Movement" is one of the reasons why the Indonesian Muslim middle class is interesting to be discussed again. Studies on the Muslim middle class in Indonesia have basically been carried out since the 1970s until now. With the abundance of literature on the Muslim middle class in Indonesia, on this basis this article aims to map out existing studies of the Muslim middle class. This article is a meta-analysis study that uses a literature study approach. Literature such as journals and articles are collected through online tools such as google and publis or perish 7 by searching using two keywords namely “Indonesian Middle Class” and “Indonesian Muslim Middle Class”. This study finds that there are three patterns of study of the Muslim middle class in Indonesia: first, the study of the politics of the Muslim middle class; the second is a study of the ideology of the Muslim middle class in Indonesia; The third study is about the lifestyle of the Muslim middle class. There were 12 articles that discussed the politics of the Muslim middle class in Indonesia. For the study of the ideology of the Muslim middle class found as many as 5 articles. Meanwhile, 39 articles were found discussing the lifestyle of the Muslim middle class in Indonesia. In the end, this study concludes that the study of the Muslim middle class in Indonesia is more dominant in discussing behavioral aspects than theoretical and conceptual aspects.